Influence of adult diet on fitness and reproductive traits of the egg parasitoid Anagrus virlai (Hymenoptera: Mymaridae), a potential biocontrol agent against the corn leafhopper. (6th May 2020) - Hill, Jorge Guillermo; Aguirre, María Belén; Bruzzone, Octavio Augusto; Virla, Eduardo Gabriel; Luft Albarracin, Erica
Abstract: Dalbulus maidi s is the most important leafhopper pest of maize in the Americas. Anagrus virlai is an egg parasitoid commonly associated with the corn leafhopper. We evaluated whether the performance of A. virlai is dependent on different diets provided during 24 hr or throughout adult female lifetime. Additionally, functional response of A. virlai on D. maidis eggs using maize leaves containing honeydew plus honey was described. A. virlai is a mostly pro‐ovigenic autogenic species whose females are able to parasitize eggs immediately after emergence. We found that wasps oviposit the majority of their eggs in the first day of their adult life. Realized lifetime fecundity and lifetime potential fecundity did not differ significantly among treatments, but longevity and egg production increased when honey was added to diet. Data were consistent with an intermediate functional response between type II and III, but closer to type II, indicating a high parasitism rate at low host densities and a decrease in the oviposition rate at high host densities, due to a possible egg limitation. Our results suggest that carbohydrate food sources (honeydew and honey) might not be the factor limiting reproductive success during the first 24 hr. Food supply, however, might influence egg maturation and survivorship of wasps, thus potentially enhancing biological pest control when hosts are scarce in the course of the first few days of adulthood.